2014
DOI: 10.5194/amt-7-2615-2014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cloud supersaturation by size-resolved aerosol particle and cloud condensation nuclei (CCN) measurements

Abstract: Abstract. In this study we show how size-resolved measurements of aerosol particles and cloud condensation nuclei (CCN) can be used to characterize the supersaturation of water vapor in a cloud. The method was developed and applied during the ACRIDICON-Zugspitze campaign (17 September to 4 October 2012) at the high-Alpine research station Schneefernerhaus (German Alps, 2650 m a.s.l.). Number size distributions of total and interstitial aerosol particles were measured with a scanning mobility particle sizer (SM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
7
25
0
1
Order By: Relevance
“…According to Krüger et al (2014), the error in N CCN is based on the counting error of the measured particle number and is 10 % of N CCN for large concentrations; given that mostly low concentrations prevailed, the mean error was about 20 % of N CCN .…”
Section: Cloud Condensation Nucleimentioning
confidence: 99%
“…According to Krüger et al (2014), the error in N CCN is based on the counting error of the measured particle number and is 10 % of N CCN for large concentrations; given that mostly low concentrations prevailed, the mean error was about 20 % of N CCN .…”
Section: Cloud Condensation Nucleimentioning
confidence: 99%
“…For clarity throughout the discussion, we subdivided the S range according to Reutter Furthermore, we marked the range, in which average peak supersaturations at cloud base, Scloud (DH,κ), in the ATTO region are expected. The Scloud(DH,κ) results were obtained according to Krüger et al (2014) and can be found in our part 1 study as well as in Table 2 of the present work. The relevant Scloud(DH,κ) range spans from ~0.18 % to ~0.34 % and, thus, overlaps with the interphase between low and intermediate S regimes.…”
Section: Overview Of Ccn Efficiency Spectramentioning
confidence: 99%
“…For further CCN-relevant information, we refer the reader to Rose et al (2008) and Krüger et al (2014). The CCN efficiency spectra parameterization as introduced in part 1 plays a key role in the present manuscript.…”
Section: Ccn Measurements and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to Krüger et al (2014), the error in N CCN (S) based on the counting error in the measured particle number ( c = √ c + 1) can be calculated by…”
Section: B1 Calculating Se Ccnmax and Se Ccnminmentioning
confidence: 99%